2018
DOI: 10.1016/j.mex.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

One-step wet chemical synthesis of gold nanoplates on solid substrate using poly-l-lysine as a reducing agent

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Previously, many attempts have been done to produce high yield of nanoplates by investigating the seeding process [ 35 ], growth aging period [ 17 ] and the materials, i.e. surfactants and capping agents used in the synthesis process [ 28 ] and also simplifying the process [ 36 ]. As a result, we found that the implementation of PLL in the synthesizing process successfully promotes high yield of Au nanoplates product especially for hexagon shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, many attempts have been done to produce high yield of nanoplates by investigating the seeding process [ 35 ], growth aging period [ 17 ] and the materials, i.e. surfactants and capping agents used in the synthesis process [ 28 ] and also simplifying the process [ 36 ]. As a result, we found that the implementation of PLL in the synthesizing process successfully promotes high yield of Au nanoplates product especially for hexagon shapes.…”
Section: Introductionmentioning
confidence: 99%
“…14,41 Then, the GNPs on the substrate have been deposited using single-step procedure with the surface density in the range of 14.47% to 48.99%. 47 However, the absorption spectrum shows no strong surface plasmon resonance band observed at ultraviolet-visible (UV-Vis) and infrared region. Besides, process parameters effect such as growth time, 14 seeding time 32 and many others onto the formation of GNPs also been studied.…”
Section: Introductionmentioning
confidence: 99%